Globalization and "Minority" Cultures The Role of "Minor" Cultural Groups in Shaping Our Global Future - Croisy, Sophie (Studies in International Minority and Group Rights, 2014)
Globalization and "Minority" Cultures: The Role of "Minor" Cultural Groups in Shaping Our Global Future is a collective work which brings to the forefront of global studies new perspectives on the relationship between globalization and the experiences of cultural minorities worldwide. These perspectives are crucial to the process of questioning contemporary global values and practices, and contribute to current debates in a variety of fields (politics, education, culture, the economy, etc.) on the causes, consequences and future of globalization. The book develops new theories and practices of transculturality that link different theoretical and cultural spheres ("minor" and "dominant") in order to formulate new discussions and propositions about appropriate responses to give in defiance of the adverse effects of globalization.